Finite element modelling to predict reinforced concrete corrosion-induced cracking - Castorena González, José H.; Gaona Tiburcio, Citlalli; Bastidas, David M.; Núñez Jaquez, Rosa E.; Bastidas, José María; Almeraya Calderón, Facundo (Consejo Superior de Investigaciones Científicas, 2019)
A finite element (FE) method was proposed to calculate the corrosion penetration depth (rcrit) on steel reinforcement necessary for the first visible crack to appear on the concrete cover. The FE analysis was carried out using the commercial software from ANSYS. The obtained FE method is a function of free concrete cover depth (C), reinforcement diameter (D), length of the anodic zone (L), and concrete type. The results show a strong influence of localized corrosion (small-size anode versus large-size cathode) on the prediction of the rcrit value. This influence can only be analysed three-dimensionally. The proposed FE method is validated with experimental results from literature. This approach is a novelty in considering the longitudinal direction in the analysis to account for the extension of the anodic cell. Corrosion type strongly depends on the C/L ratio, this leads to uniform corrosion for values between 0.02<C/L<0.1 and localized corrosion for values between and localized corrosion for values between 0.5<C/L<4.0.